Cultivation of microalgae nannochloropsis sp. In palm oil mill effluent for biodiesel production - Karthiani, Kanagesan (2022)
Extensive usage of fossil reserves resulted in rapid fossil fuel depletion. Biodiesel is one of the renewable energy alternatives designed to reduce reliance on fossil fuels. The generation of biodiesel from edible and non-edible crops is not identified as an ideal substitute to fossil fuels due to the competition for limited cultivable land proposed to cultivate crops for human consumption. To overcome the drawback, biodiesel is derived from the cultivation of microalgae. However, the cultivation of microalgae is costly as they require nutrients and water in a large amount. As a result, palm oil mill effluent (POME), which contains a large number of nutrients required for microalgae growth, is used as an alternative nutrition medium for microalgae cultivation while treating wastewater. In this study, attempts have been made to isolate and mass cultivate high lipid content microalgae from Teluk Cempedak, Kuantan coast, for biodiesel production. Among the collected samples, six microalgae were screened upon preliminary screening for morphological studies however green microalgae Nannochloropsis sp. was identified to be the most suitable microalgae with a high growth rate and abundant lipid content. Culture factors influencing the intracellular lipid body were investigated. The effect of different POME concentrations, photoperiod regimes and light-emitting diode (LED) light wavelengths were examined to determine the optimum factor for Nannochloropsis sp. growth and lipid enhancement. The mass cultivation under combined optimized culture factors of Nannochloropsis sp. followed by the Soxhlet extraction method yielded a lipid content of 61.5%. The extracted lipid was then transesterified with methanol to produce methyl esters (biodiesel) in 1.5 h, where potassium hydroxide (KOH) was used as a homogenous catalyst. Thin-layer chromatography (TLC) was done to ensure the conversion of Nannochloropsis sp. oil to biodiesel. The highest fatty acid methyl ester (FAME) formation from Nannochlropsis sp. was 80.24%. The output of gas chromatography- mass spectrometry (GC-MS) analysis proves that FAME comprises of high amount of oleic acid (C18:1) 66.13% and palmitic acid (C16:0) 12.38% respectively. Nannochloropsis sp. is a promising candidate for biodiesel production due to its composition of fatty acids and higher lipid content.